RUGBY SEVENS MATCH DEMANDS AND MEASUREMENT OF PERFORMANCE: A REVIEW (Kinesiology, 2018)
The purpose of this review is to summarize the research that has examined the match demands of elite-level, men’s rugby sevens, and provide enhanced understanding of the elements contributing to successful physical and technical performance. Forty-one studies were sourced from the electronic database of PubMed, Google Scholar and SPORTDiscus. From these, twelve original investigations were included in this review. Positive match outcomes are the result of an interplay of successful physical, technical, and tactical performances. The physical performance of players (activity profile measurement from GPS) includes high relative total distance and high-speed distance values in comparison to other team sports. The technical performance of players (skill involvement measurement from match statistics) involves the execution of a range of specific offensive and defensive skills to score points or prevent the opponent from scoring. The factors influencing change in these performance constructs has not been investigated in rugby sevens. There is a paucity in the literature surrounding the situational and individual factors affecting physical and skill performance in elite rugby sevens competition. Future studies should investigate the factors likely to have the strongest influence on player performance in rugby sevens. This should include larger sample sizes and account for repeated measures within players. This will allow coaches and scientists to improve their interpretation of activity and skill profile data, and make more informed decisions on players’ athletic preparation program.Key words: physical factors, technical factors